Study of recombination reactions of particles adsorbed on fractal and multifractal substrata - Albano, Ezequiel Vicente (1988)
Recombination reactions of adsorbed particles on fractal and multifractal media are discussed within the framework of the random walk arguments. Theoretical results, which predict anomalous reaction orderX>2 in the low coverage regime, are checked by means of Monte Carlo simulations on two-dimensional structures and good agreement is found. Thermal desorption experiments on rough surfaces are simulated by studying temperature programmed reactions on fractal percolating clusters. For this case the simulations giveX≅2.5, i. e. the fractal reaction order is greater than the classical one (X=2). The influence of chemisorbed impurities (poison) on the recombination reaction is also studied and the reaction order is found to increase beyondX=2.5 when increasing the concentration of poison. Isothermal (recombination) desorption from energetically heterogeneous surfaces is simulated on two-dimensional substrata with multifractal distributions of activation energy of diffusion. For this caseX (withX>2) depends on the energetic heterogeneity of the substrata (X=2 for an homogeneous substratum). The obtained results point out that the fractal chemical kinetic behaviour is not only restricted to the low concentration regime, but it also covers the medium coverage regime, i.e. it holds for a monolayer surface coverageθ≦0.4 in fractal percolating clusters.